El Panóptico digital de la protección de datos personales en Colombia (2018)
This article describes as a first step, the surveillance in society of disciplinary control in light of the panoptic method of Jeremy Bentham and its link to the digital ecosystem and the “transparency” of the 21st century in the face of the protection of the right to privacy of the personal information, in scenarios of technological and informational pluralism where the integral governance of the data is required by the different operators and private and public organizations, which are called to implement inclusive and protectionist privacy policies both in the physical environment and in the field of Internet, as well as social interaction and human economic and political development in the framework of a globalized economy.Likewise, this thematic approach makes an approach to the legal regime of the protection of personal data in Colombia, which has some security mechanisms and surveillance of the information that identifies its citizens but at the same time they are insufficient compared to the era technological, where there is big data or large data in information platforms without a real control that allows to establish limits to the treatment of these that leads to the identification, identification, profiling, of people with economic purposes and without responsibility for the inadequate use of digital services that puts your private life at risk.